2013
DOI: 10.1016/j.hemonc.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thyroid cancer in the Kingdom of Saudi Arabia, 2000–2010

Abstract: Thyroid cancer incidence rates have increased exponentially between 2000 and 2010 and there is significant geographical variation in the incidence of thyroid cancer throughout the Kingdom. Thyroid cancer has become the second most common cancer among young Saudi women with a male to female ratio at 0.3:1. Rising incidence of thyroid cancer in Saudi Arabia may be due to the increased detection and diagnosis of the thyroid cancers and not only an increase in the true occurrence of thyroid cancer. More studies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 22 publications
15
100
1
3
Order By: Relevance
“…In two excellent review articles covering cancer epidemiology in Arab world and South East Asia, researchers also concluded thyroid carcinoma to be second commonest cancer in Saudi females (Salim et al, 2009, Salim et al, 2010. These findings have recently been confirmed in the KSA by Hussain et al (2013). From other Arab countries, Abdulkareem (2010), did a prospective study on thyroid biopsies in Iraq.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In two excellent review articles covering cancer epidemiology in Arab world and South East Asia, researchers also concluded thyroid carcinoma to be second commonest cancer in Saudi females (Salim et al, 2009, Salim et al, 2010. These findings have recently been confirmed in the KSA by Hussain et al (2013). From other Arab countries, Abdulkareem (2010), did a prospective study on thyroid biopsies in Iraq.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly in a recent study from Turkey, Yildiz et al (2014), report 216 thyroid carcinoma which account for 13.6% of their thyroidectomies and concluded that there is a significant increase in the frequency of papillary and micropapillary carcinoma while comparing their two study periods. Within the KSA, Hussain et al (2013), from Riyadh report that a total of 2292 patients with thyroid cancer were treated from 2000 to 2010. Thyroid cancer constitutes about 9% of all malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This may stem from a difference in attitude and consciousness with regard to radiation risk in the aftermath of the Chernobyl accident. More PTCs are diagnosed among populations with wider access to healthcare in recent reports [32][33][34]. Markers for higher levels of health care access, both sociodemographic and age-based, are associated with higher PTC incidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, thyroid cancer incidence rates have increased exponentially between 2000 and 2010 with significant geographical variation, now the second most common cancer among young Saudi women with a male to female ratio at 0.3:1 (Hussain et al, 2013). Size of young population and social determinants may be important effective elements for differences in survival, which should be taken more into consideration in managing chronic disease such as thyroid cancer (Khayamzadeh et al, 2011) In China both incidence and mortality of thyroid cancer are higher in females than in males, 3.38 and 1.75 times higher in urban than rural areas, the incidence showing annually increase of 14.5% while the mortality increased by 1.42% (Liu et al, 2012).…”
Section: Thyroidmentioning
confidence: 99%